2022
DOI: 10.3389/feduc.2022.928996
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of training among non-traditional students in higher education: Testing the theory of planned behavior

Abstract: This study tested the predictive validity of Ajzen’s theory of planned behavior with a sample of 182 non-traditional students in higher education to develop our understanding of non-traditional students’ intentions to transfer trained knowledge and skills from university courses to the workplace. After completing their courses, a survey measured behavioral, normative, and control beliefs, transfer attitudes, perceived social norms, transfer self-efficacy, and transfer intentions. One year later, a follow-up su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…This valence appraisal determines individuals’ willingness to execute an activity (i.e., readiness for action, of which transfer intention is an example) and, subsequently, action (De Brabander & Martens, 2014). These assumptions are in line with transfer of training literature that showed that different types of transfer motivation predict transfer intention (Gegenfurtner, 2013; Gegenfurtner & Quesada-Pallarès, 2022) and that transfer intention predicts transfer of training (Gegenfurtner, 2013; Gegenfurtner & Testers, 2022). Figure 2 provides an overview of the expected relationships between the valences, readiness for action and action.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…This valence appraisal determines individuals’ willingness to execute an activity (i.e., readiness for action, of which transfer intention is an example) and, subsequently, action (De Brabander & Martens, 2014). These assumptions are in line with transfer of training literature that showed that different types of transfer motivation predict transfer intention (Gegenfurtner, 2013; Gegenfurtner & Quesada-Pallarès, 2022) and that transfer intention predicts transfer of training (Gegenfurtner, 2013; Gegenfurtner & Testers, 2022). Figure 2 provides an overview of the expected relationships between the valences, readiness for action and action.…”
Section: Introductionsupporting
confidence: 82%
“…Moreover, support from the work floor (e.g., supervisory support and availability of necessary resources) has been found to be a predictor of transfer motivation (Massenberg et al, 2017; Salamon et al, 2022). Based on the theory of planned behaviour (Ajzen & Fishbein, 2008) and expectancy-value theory of achievement motivation (Wigfield & Eccles, 2000; Eccles & Wigfield, 2020), possible direct effects are anticipated as well, and such effects have been found in previous studies investigating the UMTM (De Brabander & Glastra, 2018a; de Brabander & Martens, 2018b; De Brabander & Glastra, 2021) and also in the transfer of training literature for self-efficacy (Gegenfurtner & Testers, 2022). Figure 3 provides an overview of the expected relationships between sense of personal competence, perceived external support, feasibility appraisal and the valences.…”
Section: Introductionmentioning
confidence: 81%
“…They propose additional research where both TPB and the LTSI are combined to better understand the psychological processes and variables involved in all phases of the transfer process. In this study, we have answered this call and complemented previous research on transfer intentions [20,35,39,[41][42][43][44][45] by combining Ajzen's well-established socio-psychological theory of planned behavior and Holton et al's extensively tested Learning Transfer System Inventory to investigate in what way performance outcomes expectations, organizational openness to change, and transfer self-efficacy relate to the non-traditional learners' intention to transfer their newly acquired generic information literacy competencies to multiple contexts: to their study environment at the Open University and their educational work environments.…”
Section: Transfer Of Learning: a Longitudinal Processmentioning
confidence: 69%
“…Personal and contextual antecedents of task-specific motivation (e.g., transfer motivation) and behavior (e.g., transfer of training) that the UMTM identifies can be linked to factors that have been found to influence transfer of training [6,7,12,[38][39][40][41][42]. For example, personal feelings of autonomy translate to sense of personal autonomy in the UMTM, whereas social norms and supervisor support are similar to subjective norm and perceived external support of the UMTM.…”
Section: Figurementioning
confidence: 99%